2013
DOI: 10.1017/erm.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

T regulatory cells in childhood arthritis – novel insights

Abstract: In recent years, there have been many new developments in the field of regulatory T cells (Treg), challenging the consensus on their behaviour, classification and role(s) in disease. The role Treg might play in autoimmune disease appears to be more complex than previously thought. Here, we discuss the current knowledge of regulatory T cells through animal and human research and illustrate the recent developments in childhood autoimmune arthritis (juvenile idiopathic arthritis (JIA)). Furthermore, this review s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 160 publications
(229 reference statements)
3
25
0
Order By: Relevance
“…Interestingly, while T H 1-like Tregs maintained their immunomodulatory role in liver transplant recipients with normal allograft function, similar to previous reports (33-35), in the setting of inflammation (i.e. in transplant recipients with de novo autoimmune hepatitis), these Tregs lost the ability to suppress effector cell proliferation (Figure 3B-C).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, while T H 1-like Tregs maintained their immunomodulatory role in liver transplant recipients with normal allograft function, similar to previous reports (33-35), in the setting of inflammation (i.e. in transplant recipients with de novo autoimmune hepatitis), these Tregs lost the ability to suppress effector cell proliferation (Figure 3B-C).…”
Section: Discussionsupporting
confidence: 89%
“…The function of T H 1-like Tregs has been variably reported as suppressive by some investigators (33-35) and non-suppressive by others (28). Having demonstrated that sorted Tregs from subjects with de novo autoimmune hepatitis lost their immunoregulatory function as well as demonstrating that a pro-inflammatory cytokine milieu within the liver in de novo autoimmune hepatitis can drive IFN-γ secretion from FOXP3 + Tregs, we next questioned if IFN-γ blockade would restore Treg function.…”
Section: Resultsmentioning
confidence: 99%
“…These findings imply that iaT reg selectively expand in active disease from T eff , consistent with the origin of T reg type 1 (Tr1) cells [93]. iaT reg may be unsuccessful at restraining these effector responses in vivo due to T eff resistance to T reg -mediated suppression -such as protein kinase B hyperactivation in JIA and secretion of TNF-related apoptosis-inducing ligand (TRAIL) in RA by effector cells -in combination with the proinflammatory milieu [94][95][96][97]. The deep sequencing technologies used for TCR repertoire profiling in these studies are advantageous in that these methods do not rely on prior (auto)antigen knowledge, which poses a major hurdle in autoimmune diseases where multiple putative autoantigens exist or where autoantigens are still yet to be defined [98,99].…”
Section: Tcr Bias Oligoclonal T Cell Expansion In Ra Patientsmentioning
confidence: 56%
“…While iaT reg are ontogenically related to the T reg cell lineage, they share substantial TCR repertoire overlap with pathogenic synovial effector T cells (T eff ) and blood CPLs [92]. iaT reg may be unsuccessful at restraining these effector responses in vivo due to T eff resistance to T reg -mediated suppression -such as protein kinase B hyperactivation in JIA and secretion of TNF-related apoptosis-inducing ligand (TRAIL) in RA by effector cells -in combination with the proinflammatory milieu [94][95][96][97]. iaT reg may be unsuccessful at restraining these effector responses in vivo due to T eff resistance to T reg -mediated suppression -such as protein kinase B hyperactivation in JIA and secretion of TNF-related apoptosis-inducing ligand (TRAIL) in RA by effector cells -in combination with the proinflammatory milieu [94][95][96][97].…”
Section: Tcr Bias Oligoclonal T Cell Expansion In Ra Patientsmentioning
confidence: 99%
“…RA patients have been reported to exhibit a higher frequency of Th17 like T regs compared to healthy subjects [86]. These T regs also produce IFN-γ, IL-2, ROR-γt and Tbet, along with IL-17A [87,88]. However, the ability of these cells to suppress proliferation, production of IFN-γ and IL-2 in effector T cells was comparable to those of conventional T reg subpopulation from healthy controls, suggesting that these T regs are not reprogrammed to lose their suppressive capacities.…”
Section: Pro-inflammatory Cytokine Production In Foxp3+ Tregs Is Amentioning
confidence: 99%